Farmer perception and valuation of seed quality: Evidence from bean and cowpea seed auctions in Tanzania and Ghana - Maredia, Mywish K.; Shupp, Robert; Opoku, Edward; Mishili, Fulgence; Reyes, Byron A.; Kusolwa, Paul; Kusi, Francis; Kudra, Abdul (Wiley, 2019)
Double blind field experiments and experimental auctions were conducted with bean and cowpea farmers in Tanzania and Ghana to gauge the relative demand for three types of seed products that differ in price and quality: certified, quality declared, and recycled. Whether the cost differential makes these seeds qualitatively different products as reflected in their perceived performance, and whether that translates into farmers’ willingness to pay price premiums, are the research questions addressed by this study. Results indicate that, all else equal, there were significant differences in the perceived quality of the seed products evaluated. Farmers were willing to pay significantly more for their higher rated seed relative to their lower rated seeds. However, for a majority of farmers the magnitude of the premium they are willing to pay for a higher quality seed is less than the current price differential between certified seed and grain. Research and policy implications of these results for legume seed system are discussed.